Spiny Amaranth (spiny pigweed) Control in Pastures - Jason A. Ferrell; Brent Sellers (EDIS, 2007)
SS-AGR-288, a 3-page illustrated fact sheet by Jason Ferrell and Brent Sellers, describes this summer annual with sharp spines which is common in Florida pastures, especially around feeding pens and water troughs. Includes control recommendations. Published by the UF Department of Agronomy, October 2007.